Pattern of common skin conditions among school children in an urban area of a district in coastal Karnataka: a cross-sectional study - A. U., Shameena; Badiger, Sanjeev; S., Nanjesh Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Overcrowding, Poor personal hygiene and Lower economic status are proved to be major causes of common skin conditions. School children are more prone for these infections and majority of them are preventable. The objective of the study was to assess the pattern of common skin conditions among school children in Urban South India. Methods: A cross sectional study was conducted on 615 children from three primary schools coming under the community health centre, Mulky. Data was collected using a pretested semi structured questionnaire on socio-demographic characteristics and skin conditions were identified by examination. Results: Out of the 615 children, 389 (63%) had infective skin conditions. Most of them belonged to Hindu religion (57.4%) followed by Muslim (32.7%) and Christian (9.4%). Skin infections were equal among both sexes. Among the skin infections, nearly 26.1% had fungal infections, 18.7% had bacterial infections, 13.1% had parasitic infections and 5.4% had viral infections. Conclusions: Prevalence of skin infections is high in our study and there is a need to emphasize more on improving school health programmes and health education to teachers, parents and children.